Automated grass cutter using voice recognition - Muhamad Salihin, Nasir; Adam, Samsudin; Ezzatul Farhain, Azmi; Norhafizah, Md Sarif; Azmirul, Ashaari; Nur Aiman Hanis, Hasim (Asian Research Publishing Network (ARPN), 2021)
Grass cutter is one of the significant home appliances especially among the country side. The existing grass cutter machine in agriculture field usually using kerosene as their fuel source to operate the machine. However, by using fuel source, combustion process will occur and will pollute the environment with toxic gas which can lead to thinning of ozone layer and disease. Moving to improvement of grass cutter machine, we can conclude that with the improvement of the machines comes greater prices. This will make the people comes hard to buy the expensive one. Due to the high price, many people will buy the cheaper machines which they can afford. This can be seen easily in Malaysia where we can see many people will use the string trimmer to cut the grass. The string trimmer is a semi manual machines which requires humans to use it to cut the grass. The machines are quite heavy and after a period of time using the machines; it will lead to shaking and back-ache of the user. This will lead to serious safety issues. The idea of controlling a grass cutter machines is quite simple with the use of Arduino and some electrical devices. The grass cutter machines are control by Arduino which control the directions to moves forward, backward, right, left and stop. The control of direction is being help with the use of L298N motor driver which receive the signal from the Arduino to control the direction of the motor. Besides, it uses a simple voice recognition that all user can get from Google Play store to communicate with the grass cutter machines. The motor has two roles in this system which is to control the direction of grass cutter and also the cutting process of the machines. At last, the goal of creating this grass cutter machines are to create a low cost machines where all people can buy it thus preventing a health issues to the user and also creating a low budget grass cutter machines where all user can afford.